Plasma leucine-rich α-2 glycoprotein 1 in ST-elevation myocardial infarction: vertical variation, correlation with T helper 17/regulatory T ratio, and predictive value on major adverse cardiovascular events - Luo, Ting; Jiang, Xiaoli; Zhang, Zhenzhen; Gao, Ming; Wang, Hao (Frontiers in Cardiovascular Medicine, 2024)
Objective: Leucine-rich α-2 glycoprotein 1 (LRG1) promotes inflammation and myocardial injury, but its clinical role in ST-elevation myocardial infarction (STEMI) is rarely disclosed. Herein, this prospective study aimed to explore the value of plasma LRG1 at different timepoints to predict major adverse cardiovascular event (MACE) risk in STEMI patients.In total, 209 STEMI patients were enrolled for determining plasma LRG1 at admission and on day (D)1/D7/D30 after admission via enzyme-linked immunosorbent assay, as well as for determination of peripheral blood T helper 17 (Th17) cells and regulatory T (Treg) cells by flow cytometry. Additionally, plasma LRG1 was obtained from 30 healthy controls at enrollment.Results: LRG1 was increased in STEMI patients at admission compared with healthy controls (P<0.001). In STEMI patients, LRG1 varied at different timepoints (P<0.001), which elevated from admission to D1, and gradually declined thereafter. LRG1 at admission was positively associated with Th17 cells (P=0.001) and Th17/Treg ratio (P=0.014). LRG1 at admission (P=0.013), D1 (P=0.034), D7 (P=0.001), and D30 (P=0.010) were increased in patients with MACE compared to those without. LRG1 at D7 exhibited good ability to estimate MACE risk (area under curve=0.750, 95% confidence interval=0.641-0.858). LRG1 at admission>60 μg/mL (P=0.031) and D7>60 μg/mL (P=0.018) linked with increased accumulating MACE. Importantly, LRG1 at D7>60 μg/mL was independently correlated with increased MACE risk (hazard ratio=5.216, P=0.033).Plasma LRG1 increases from admission to D1 and gradually declines until D30, which positively links with Th17 cells and MACE risk in STEMI patients.